INDUSTRY INITIATIVE TO REPEAL SAN FRANCISCO OFFICE SMOKING RESTRICTION ORDINANCE - CHERRY,JR (Tufts Archival Research Center, 2007)
Memo from J R Cherry regarding Lorillard's industry initiative to repeal the San Francisco workplace smoking restriction ordinance. Discusses recommendation that efforts should be made to secure signatures for a petition and that an attitude survey should be underway. Announces formation of a local committee to carry the project forwards. Lists members of the committee.